Who do you think you are : understanding personality from the inside out - Thomas, Tina (Morgan James Publishing : Made available through hoopla, 2016)
As Dr. Thomas explains, "There is no such thing as a difficult person, just people with difficult personalities!" Those who understand personality and its biological basis never look at themselves or others in the same way again. Understanding personality this way will help you to understand what motivates you and others. This will also improve your ability to communicate. "Who Do You Think You Are" will teach you how to adjust your internal and external environments to optimize your specific personality chemistry to become the person you always hoped you could be and create the life circumstances you only dreamed were possible. And, if that isn't extraordinary enough, this new knowledge will create more compassion within yourself and more peace within all the relationships you ever had, have now, or will have in the future. Understanding yourself from the inside out may be the single most important body of information you ever need to reach your full potential. Who do you think you are? You may be delighted and surprised when you discover yourself this way!